Analisis Terhadap Implementasi Pembelajaran Aqidah Akhlak dalam Pembentukan Karakter Religius Siswa di SMP Muhammadiyah 1 Purwokerto - Arinda Nina Pramahesti; Makhful Makhful (Proceedings Series on Social Sciences & Humanities, 2023)
Forming students with character is an educational task, namely building a whole person, namely a good human being and also with character. There is one subject at school or at the madrasa that can shape the character of students, namely the subject of moral aqidah. The formation of students' morals can be done through formal or non-formal education, namely through learning aqidah morals. Aqidah morality is the foundation of belief for a Muslim who has a very large role in his life. The purpose of this study was to determine the implementation of moral aqidah learning in the formation of students' religious character and to find out the supporting and inhibiting factors in learning moral creed in forming religious character in SMP Muhammadiyah 1 Purwokerto. This research is a type of field research with observation and interview techniques. Data analysis uses a descriptive approach, namely by examining the data, examining all available data from various sources, summarizing and focusing on the important things. The results of this study indicate that the implementation of akhidah akhlak learning that has been carefully and in detail in or to form the religious character of students at SMP Muhammadiyah 1 Purwokerto includes: fist, There is an application of the akhidah akhlak learning material; Second, There is a positive attitude change in students from learning akhidah akhlak; Third, Students can distinguish commendable and despicable attitudes and apply them in everyday life. 4). Religious values ??shown by students by diligently worshiping, respecting teachers and parents, and being grateful for God's gifts by giving infaq; Fourth, The value of caring. The supporting factor is inseparable from the efforts of akhidah akhlak teachers and other general subject teachers. And also a supportive school environment to shape the character of religious students. While the inhibiting factor was the discovery of some students who were still talking to themselves in class and also some children who were less disciplined. Then the importance of the teacher in guiding not only teaching but in guiding students to become good individuals.